Assessing the suitability of Anthonomus morticinus Clark (Coleoptera: curculionidae) on Solanum mauritianum Scopoli (Solanaceae) - Mkhomazi, Vusumuzi Lucky (My University, 2023)
Solanum mauritianum Scopoli (Solanaceae) is an invasive weed with detrimental impacts in South Africa. Since 1984, biocontrol efforts have been made to manage the weed, with only two agents, Anthonomus santacruzi Hustache (Coleoptera: Curculionidae), and Gargaphia decoris Drake (Tingidae) being released to date. These agents have a low impact on S. mauritianum, and hence there is a need for more candidate agents to be tested in order to improve the biocontrol of S. mauritianum in South Africa. Anthonomus morticinus Clark (Coleoptera: Curculionidae) was imported from Uruguay to assess its fecundity and longevity on S. mauritianum, its host specificity and risk analysis on solanaceous agricultural plants, as well as its thermal tolerance in terms of climate suitability. CLIMEX software was used to predict the potential of A. morticinus establishing in South Africa, by relating its cold tolerance to the minimum winter temperatures in regions where S. mauritianum is found in South Africa. Anthonomus morticinus has a similar biology to A. santacruzi, with its larvae developing inside flowers and buds of S. mauritianum. From egg to adult, A. morticinus takes 19-30 days to complete its development at room temperature and relative humidity (T= 25.6 °C, RH= 49%). The larval phase takes about 18 days to complete, with pupation ranging from 4-7 days before an adult weevil emerges. The weevils live between 21 and 105 days, and each female produces 28 larvae on average. It was found that A. morticinus exhibited non-target feeding only on Solanum species, and no feeding was observed on selected agricultural plants outside the genus, during no-choice tests. Oviposition and development by A. morticinus was found on four of the five tested S. melongena (eggplant) varieties used in no choice tests. In paired choice tests, feeding and oviposition was greater on S. mauritianum than all the other test plants. The non-target feeding risk was highest on S. melongena (black beauty variety), followed by S. melongena (little finger), S. melongena (violet moon), and S. melongena (black king). The non-target reproductive risk was lower in all the eggplant varieties (< 1%), with S. melongena (black king F1 hybrid) having no reproductive risk. Anthonomus morticinus had a CTmin = 1.71 °C and was significantly more cold tolerant than A. santacruzi (CTmin = 4.93 °C). The CTmin of A. morticinus was lower than the low winter temperatures experienced anywhere in South Africa where S. mauritianum is found, and the average CTmin of A. santacruzi (tested concurrently) was higher than the low winter temperatures of the Midlands and the Highveld S. mauritianum sites. In addition, A. santacruzi lethal limits (LT50 = -5.8 °C, n= 90) were relatively higher than A. morticinus (LT50 = -9.5 °C, n= 130). Although more host specificity tests are required with A. morticinus on Solanaceae plants, the results, so far, are promising and suggest that A. morticinus may be a suitable, cold tolerant agent of S. mauritianum. The biological relationship of A. morticinus with S. mauritianum is similar to the one exhibited by A. santacruzi on S. mauritianum. Given that A. morticinus gets released, these two Anthonomus spp. may work effectively to improve the biocontrol of S. mauritianum, as A. morticinus should establish and overwinter further inland in South Africa than its congener.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2022